Efficacy and Safety of Bisphosphonates for Fracture Prevention in Osteoporosis: Systematic Reviews and Indirect Treatment Comparisons - Maher, Maurica (Université d'Ottawa / University of Ottawa, 2014)
Osteoporosis is a growing cause of morbidity and mortality in aging populations worldwide, especially in postmenopausal women. Bisphosphonates are widely prescribed for fracture prevention in osteoporosis. Meta-analyses have been performed for alendronate, risedronate, and etidronate, examining their effectiveness versus placebo in fracture prevention. Total withdrawals and adverse event withdrawals were examined as safety outcomes. Systematic reviews were performed for two other bisphosphonates, ibandronate and zoledronic acid and the results combined with previously obtained data for the other bisphosphonates. Indirect treatment comparisons of the drugs against each other and versus placebo were performed using Bayesian and frequentist methods. Both types of analyses yielded almost identical results: zoledronic acid and alendronate were the most effective bisphosphonates for preventing vertebral fractures. No differences were found regarding withdrawals. Subgroup analyses found that fracture prevention was generally more effective with longer therapy (greater than or longer than 3 years).
Keywords: osteoporosis; bisphosphonates; network meta-analysis; systematic reviews